Hubungan Pengetahuan dan Sikap Ibu Tentang Pemberian ASI Eksklusif - Riska Sabriana; Rika Riyandani; Ria Wahyuni; Asridawati Akib (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: Breast milk as the best food for the physical, mental and intellectual development of infants has been widely known. The benefits of breast milk will be greatly increased if the baby is only breastfed for the first 6 months of life. Every mother can breastfeed her baby exclusively. Aim: Knowing the relationship between the mother's knowledge and attitude with the provision of Exclusive Breast Milk. Method: This type of research is analytical survey research with a cross-sectional study approach. Results: Showed that mothers who did not exclusively breastfeed their babies as many as 5 people or 15.6% and mothers who gave exclusive breast milk to as many as 27 people or 84.4%. The results of the analysis found that there is a meaningful relationship between the mother's knowledge and attitude toward exclusive breastfeeding. Conclusion: There is a meaningful relationship between the mother's knowledge and attitude toward exclusive breastfeeding. Variations in maternal attitudes and knowledge provide different contributions to exclusive breastfeeding to babies. It is necessary to make efforts to improve maternal knowledge and attitudes through health counseling regarding the importance of exclusive breastfeeding